Self-assembled biodegradable herbal-based nanoflower decorative magnesium implants combine therapy with bone regeneration - Huihui Du; Dongdong Zhang; Kui Xue; Limin Ma; Ru Xu; Ji Tan; Feng Peng; Xuanyong Liu (Journal of Magnesium and Alloys)
The rapid corrosion rate and limited biological functionality still pose challenges for magnesium (Mg)-based implants in the treatment of complicated bone-related diseases in clinic. Herein, a multifunctional biodegradable curcumin (herbal medicine)-ferrum (Cur-Fe) nanoflower was self-assembled on plasma electrolytic oxidation (PEO)-treated Mg alloy via a facile immersion process to realize differential biological function for anti-bacteria/tumor and bone regeneration. The results indicated that Cur-Fe nanoflower coating can promote protein adsorption, cell adhesion and proliferation, exhibiting excellent biocompatibility. The Cur-Fe nanoflower coating exhibits unique degradation characteristics, as curcumin gradually decomposes into ferulic acid, aromatic aldehyde and other antibacterial substances, and the coating spontaneously converts into FeOOH nanosheets, ensuring the corrosion resistance of Mg-based implants. Moreover, Cur-Fe coating exhibits remarkable narrow gap semiconductor characteristics, which can generate reactive oxygen species (ROS) and demonstrated excellent antibacterial effect under simulated sunlight (SSL) irradiation. Meanwhile, under NIR irradiation, Cur-Fe coating showed excellent chemotherapy/photodynamic/photothermal synergetic antitumor properties in vitro and in vivo due to the introduction of curcumin, and photocatalysis and photothermal conversion properties of coating. Furthermore, Cur-Fe nanoflower coating demonstrated great osteogenesis activity in vitro and in vivo due to unique micro/nano structure, surface chemical bond, and the release of Mg and Fe ions.